Baseline infection prevalence, risk factors and treatment outcomes of visceral leishmaniasis in Northeastern Uganda: A cross-sectional study. - Patrick Sagaki; Jeremiah Mutwalante Twa-Twa; Posiano Mulalu; Benon Wanume; Peter Olupot-Olupot (PLoS Neglected Tropical Diseases)
Introduction Visceral leishmaniasis (VL) also known as Kala-azar is one of the neglected tropical diseases (NTD) of public health importance. Despite being a disease of a long history, the condition remains poorly studied especially in East Africa. For instance, whereas, the geographical location of the disease is known, there is a stark paucity of data on the burden, risk factors and clinical outcomes of this condition in Northeastern Uganda. Therefore, the disease picture in these settings is incomplete. The overarching aim for this study was to describe pre-elimination prevalence, associated factors and treatment outcomes of VL in Moroto District. Methods We conducted a cross-sectional study in which community cases were identified at baseline. They were followed up at Amudat Hospital Kala-azar Treatment Centre for the treatment outcomes. We used a customized data collection tool to elicit data on demographic characteristics, socio-economic and anthropometry. Data were entered on excel database and exported to Stata software for analyses. Proportions and measures of central tendency were computed. Binary associations were determined using Chi-square statistical test. In addition, variables independently associated with VL were determined via logistic regression analyses. At follow up stage, the outcomes were determined. Results The overall prevalence of VL infection in Moroto district was 5.21% (95%CI: 3.15% - 8.48%) with varying county level prevalence at Matheniko, Tepeth and Mororo at 6.90%, 4.49% and 3.61%; respectively. The common risk factors for VL infection included lack of knowledge of habitat for Sand flies, AOR 5.33 (95%CI: 1.69-16.82). Patients with VL presented with fever, headache, abdominal pain and swelling, coughing, night sweats, diarrhea, fatigue, breathlessness, and nose bleeding. The average hospitalization for VL was 17 days. All the patients who were treated at the hospital cured. Conclusion The prevalence of VL in Moroto district was 5.21% and within elimination threshold. The high-risk factors for VL infection included lack of knowledge about the habitat for Sand flies. The average hospitalization for VL was 17 days.